Politeness Strategies in Students' Interaction - Sry Wahyuni (ELT Worldwide: Journal of English Language Teaching, 2019)
This research was aimed to describe the expression that the students used in talking to others to show their politeness in doing discussion in the classroom, but not in learning environment. The researcher applied descriptive qualitative method and used recording as the only instrument. The participant of this research was the second grade student of Senior High School in SMAN 5 Barru which consisted of 21 students. The result of this research showed that there were many factors influencing the students’ politeness in communication such as situation, status, age, culture, gender, and so on. And there were two common ways that the students used in expressing their politeness which was questioning and commanding.